Velvet antler polypeptide partially rescue facet joint osteoarthritis-like phenotype in adult β-catenin conditional activation mice - Wan-qing Xie; Yong-jian Zhao; Feng Li; Bing Shu; Shu-ru Lin; Li Sun; Yong-jun Wang; Hong-xin Zheng (BMC, 2019)
Abstract Background Wnt/β-catenin signaling pathway is closely related to osteoarthritis. In our preliminary study, β-catenin conditional activation (cAct) mice that specifically over-express β-catenin gene in cartilage chondrocyte exhibits osteoarthritis-like phenotype in the lumbar disc and knee joint. Therefore, we used the mice to model FJ-OA and test the potential curative effect of Velvet Antler Polypeptide (VAP) on this mice model. Methods We tested the effect of VAP on β-catenin conditional activation mice, and used Cre negative littermates as controls. Micro-CT, histology and histomorphometry analysis were performed to evaluate the curative effect of VAP on mice facet joint-like phenotype. Expression of β-catenin and collagen II was detected by immunohistochemistry (IHC) and western-blot., MMP13, ADAMTS4 and ADAMTS5 was detected by immunofluorescence (IF). RT-PCR analysis was preformed to detect mRNA expression of cartilage degrading enzymes, such as MMP13, ADAMTS4 and ADAMTS5. Results Results of micro-CT (μCT) analysis showed that VAP could partially reverse lumbar disc osteophyte formation observed in β-catenin(ex3) Col2ER mice. Histology data revealed VAP partially improved facet joint cartilage tissue invades. Histomorphometry analysis showed an increase in total cartilage area after VAP treatment. IHC show that VAP reduced β-catenin protein levels and moderately up-regulated collagen II protein levels. RT-PCR and IF data showed that VAP down-regulated the expression of extracellular matrix synthesis (ECM) degradation enzymes MMP13, ADAMTS4 and ADAMTS5. Conclusion Taken together, VAP may modulate ECM by inhibits MMP13, ADAMTS4 and ADAMTS5 via Wnt /β-catenin signaling pathway. Velvet Antler Polypeptide may be a potential medicine for FJ-OA.